2018
DOI: 10.1155/2018/3026851
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Multidrug Resistance and Extended-Spectrum β-Lactamase Carriage of Clinical Uropathogenic Escherichia coli Isolates in Riyadh, Saudi Arabia

Abstract: The prevalence of extended-spectrum β-lactamase-producing Escherichia coli (ESBL-producing E. coli) has recently increased worldwide. This study aims at determining the antimicrobial susceptibility patterns of a collection of clinical E. coli urine isolates and evaluating the ESBL carriage of these isolates at phenotypic and genotypic levels. A total of 100 E. coli urine isolates were collected at a tertiary healthcare centre in Riyadh from January 2018 to March 2018. Antimicrobial susceptibility testing was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
68
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(119 citation statements)
references
References 59 publications
22
68
7
Order By: Relevance
“…In our study 81(57.45%) ESBL producers found whereas, in other studies, the prevalence of ESBL producers has been documented, (33%), (38.6%), (64.7%) and 34.71% respectively (Alqasim et al, 2018;Murthy et al, 2018;Bhandari et al, 2016;Aruna and Mobashshera, 2012).…”
Section: Resultscontrasting
confidence: 43%
See 1 more Smart Citation
“…In our study 81(57.45%) ESBL producers found whereas, in other studies, the prevalence of ESBL producers has been documented, (33%), (38.6%), (64.7%) and 34.71% respectively (Alqasim et al, 2018;Murthy et al, 2018;Bhandari et al, 2016;Aruna and Mobashshera, 2012).…”
Section: Resultscontrasting
confidence: 43%
“…Among the ESBL producers, E. coli 59 (41.84%) was the most frequent organisms, as shown in (Table 6). In similar studies, the prevalence of E. coli was most prevalent in Singapore (33%), Hong Kong (48%) and India 60% as reported by (Hsueh et al, 2011) 37.87% Saudi Arabia (Alqasim et al, 2018) .…”
Section: Resultsmentioning
confidence: 59%
“…To date, more than 350-different ESBL have been described and mainly are encoded in plasmids. [26][27][28] Some investigations indicated that depending on enzyme substrate, the strains can be classified as ESBL producers or carbapenemases producers. 29,30 This is important because carbapenems are in the list of last resource antibiotics for treatment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Rodrigues et al , 2016 reported resistance in CA-UTI annually and consecutively from 2010 to 2015 (13); accordingly, their study was considered as six papers. Similarly, Fasugba et al, 2016 detected the resistance in both CA and HA cases over five years; they reported ten cohorts(16) Alqasim et al, 2018. (two cohorts) compared the ciprofloxacin resistance in two E. coli strains(23).…”
mentioning
confidence: 99%
“…Similarly, Fasugba et al, 2016 detected the resistance in both CA and HA cases over five years; they reported ten cohorts(16) Alqasim et al, 2018. (two cohorts) compared the ciprofloxacin resistance in two E. coli strains(23). And so were Cia et al, 2015 who compared two groups of untreated and previously treated patients(24).…”
mentioning
confidence: 99%